The Integrated Model of Religious Moderation: Quantifying the Impact of Religiosity, Academic Culture, and Learning Environment among Indonesian Muslim Graduate Students - Akmansyah, Muhammad; Faisal, Agus; Zaelani, Abdul Qodir; Mujahid, Amin (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2025)
This study addresses the urgent need to counter religious radicalization by examining how religiosity, academic culture, and learning environments shape moderate Muslim character among Indonesian graduate students, aligning with national and global peacebuilding goals. Using a quantitative approach, data from 147 postgraduate students at UIN Raden Intan Lampung were analyzed via Structural Equation Modeling (SEM-PLS). Results revealed significant positive effects of religiosity (β = 0.41, p < 0.001), academic culture (β = 0.34, p = 0.001), and learning environment (β = 0.22, p = 0.003) on fostering moderation, collectively explaining 53.9% of its variance. Religiosity emerged as the strongest predictor, underscoring its role in cultivating inclusive attitudes, while academic practices (e.g., critical discourse) and supportive learning settings reinforced tolerance and anti-violence values. The findings propose an integrated model where spiritual, intellectual, and environmental dimensions synergize to nurture moderation, offering actionable insights for educators and policymakers to design holistic strategies against extremism. However, the single-institution sample limits generalizability, necessitating future studies across diverse universities and, qualitative explorations of contextual factors like socio-economic dynamics or media influence. By bridging theoretical and practical gaps, this research advocates harmonizing higher education systems to empower moderate Muslim leaders, advancing Indonesia’s multicultural harmony and contributing to Sustainable Development Goals (SDGs) on peace. The study underscores the imperative of embedding inclusive pedagogies and values-driven academic cultures to sustain social cohesion in pluralistic societies. Penelitian ini merespons kebutuhan mendesak dalam mengatasi radikalisasi agama dengan menelaah kontribusi religiusitas, budaya akademik, dan lingkungan pembelajaran dalam pembentukan karakter Muslim moderat di kalangan mahasiswa pascasarjana, sejalan dengan upaya perdamaian nasional dan global. Menggunakan pendekatan kuantitatif, data dari 147 mahasiswa UIN Raden Intan Lampung dianalisis melalui Structural Equation Modeling (SEM-PLS). Hasil menunjukkan pengaruh signifikan religiusitas (β = 0,41, p < 0,001), budaya akademik (β = 0,34, p = 0,001), dan lingkungan pembelajaran (β = 0,22, p = 0,003) terhadap pembentukan sikap moderat, secara kolektif menjelaskan 53,9% varian. Religiusitas menjadi prediktor terkuat, menegaskan perannya dalam menumbuhkan inklusivitas, sementara praktik akademik (misal: diskursus kritis) dan lingkungan belajar kolaboratif memperkuat nilai toleransi dan anti-kekerasan. Temuan ini menyajikan model terintegrasi yang mensinergikan dimensi spiritual, intelektual, dan lingkungan untuk mendorong moderasi, memberikan rekomendasi praktis bagi pendidik dan pembuat kebijakan dalam merancang strategi holistik melawan ekstremisme. Namun, sampel terbatas pada satu institusi mengurangi generalisasi, sehingga penelitian lanjutan perlu mencakup universitas beragam dan mengeksplorasi faktor kontekstual (seperti dinamika sosio-ekonomi atau pengaruh media) secara kualitatif. Dengan menjembatani kesenjangan teoritis dan praktis, penelitian ini mendorong harmonisasi sistem pendidikan tinggi untuk memberdayakan pemimpin Muslim moderat, mendukung harmoni multikultural Indonesia dan Tujuan Pembangunan Berkelanjutan (TPB) tentang perdamaian. Studi ini menegaskan pentingnya mengintegrasikan pedagogi inklusif dan budaya akademik berbasis nilai guna memelihara kohesi sosial di masyarakat majemuk.